Overexpression of Trypanosoma cruzi High Mobility Group B protein (TcHMGB) alters the nuclear structure, impairs cytokinesis and reduces the parasite infectivity - Tavernelli, Luis Emilio (2019)
Kinetoplastid parasites, included Trypanosoma cruzi, the causal agent of Chagas disease, present a unique genome organization and gene expression. Although they control gene expression mainly posttranscriptionally, chromatin accessibility plays a fundamental role in transcription initiation control. We have previously shown that High Mobility Group B protein from Trypanosoma cruzi (TcHMGB) can bind DNA in vitro. Here, we show that TcHMGB also acts as an architectural protein in vivo, since the overexpression of this protein induces changes in the nuclear structure, mainly the reduction of the nucleolus and a decrease in the heterochromatin:euchromatin ratio. Epimastigote replication rate was markedly reduced presumably due to a delayed cell cycle progression with accumulation of parasites in G2/M phase and impaired cytokinesis. Some functions involved in pathogenesis were also altered in TcHMGB-overexpressing parasites, like the decreased efciency of trypomastigotes to infect cells in vitro, the reduction of intracellular amastigotes replication and the number of released trypomastigotes. Taken together, our results suggest that the TcHMGB protein is a pleiotropic player that controls cell phenotype and it is involved in key cellular processes.